THE INFLUENCE OF COMPANY SIZE AND SALES LEVEL ON THE PROFIT GROWTH OF FOOD AND BEVERAGE SUBSECTOR COMPANIES - Cipta Kurnia Sandi; Sri Wahyuni Jamal; Fenty Fauziah (Universitas Nusa Cendana, 2025)
The food and beverage subsector, which is part of the primary consumption industry, has profit growth that is influenced by various internal company factors, including company size and sales level. This study aims to analyze the effect of company size and sales level on profit growth in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX). This study uses documentation as its data collecting strategy. In all, 110 pieces of observational data were collected from 10 organizations based on the sample criteria, with an observation period spanning from 2014 to 2024. Purposive sampling is the technique used to determine the sample. This research made use of multiple linear regression as its method of data analysis. According to the findings, sales volume significantly affects earnings growth, although firm size does not. Keywords: Company Size; Sales Level; Profit Growth